2006
DOI: 10.1055/s-2006-951719
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Aqueous Extracts from Species of the Lamiaceae Family against Herpes simplex Virus Type 1 and Type 2 in vitro

Abstract: Aqueous extracts from species of the Lamiaceae family were examined for their antiviral activity against Herpes simplex virus (HSV). Extracts from lemon balm (Melissa officinalis), peppermint (Mentha x piperita), prunella (Prunella vulgaris), rosemary (Rosmarinus officinalis), sage (Salvia officinalis) and thyme (Thymus vulgaris) were screened. Their inhibitory activity against Herpes simplex virus type 1 (HSV-1), type 2 (HSV-2) and an acyclovir-resistant strain of HSV-1 (ACV (res)) was tested in vitro on RC-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 14 publications
(20 reference statements)
4
105
0
6
Order By: Relevance
“…Formula to determine the virus inhibition percentage: Nolkemper et al (2006) also reported the antiviral action on both types of HSV, HSV-1 and HSV-2, in experiments using spices that presented significant reduction of these virus replications in RC -37 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formula to determine the virus inhibition percentage: Nolkemper et al (2006) also reported the antiviral action on both types of HSV, HSV-1 and HSV-2, in experiments using spices that presented significant reduction of these virus replications in RC -37 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Extracts from plants, algae and essential oils from seeds or fruits presenting compounds with antiviral effects have been the most studied items within this category. Flavonoid compounds such as quercetin revealed decrease or inhibition of the yield of Herpes simplex virus (HSV 1), and also of type 2 virus, thanks to a probable virucidal action, as the result was an inhibition of viral DNA replication (Nolkemper et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Bioactivity: Aqueous extract of Prunella vulgaris showed a high antiviral activity against Herpes Simplex Virus-1, 2 and Acyclovir (resistant) strain of HSV (Nolkemper et al, 2006). P-374 herbal therapy for endometriosis of Prunella vulgaris (Self heal) reduces the size and number of enomedriotic xenograft in immune deficient RAG -2/gamma (C) knockout mice (Collins et al, 2006).…”
Section: Use In Tsmmentioning
confidence: 99%
“…This activity is attributed to chemical constituents, such as rosmarinic acid, caffeic acid, chlorogenic acid, and ferulic acid, which inhibit viral DNA and RNA replication (Allahverdiyev et al, 2004;Jassim, Naji, 2003;British Herbal Pharmacopoeia, 1996;Dimitrova, Dimov, Manaloval, 1993). Moreover, results suggest that constituents of Melissa officinalis extract interact with structures of the virion envelope during the extracellular phase which are necessary for adsorption or entry into host cells, displaying the highest antiviral activity in vitro against HSV-1 and HSV-2 (inhibitory concentrations of 0.025 mg/mL and 0.027 mg/mL respectively) (Nolkemper et al, 2006).…”
Section: Introductionmentioning
confidence: 99%